Two cases of poorly differentiated synovial sarcoma arising from the chest wall - One case of Ewing sarcoma-like small cell type with death 4 years after the first presentation and one case of high-grade spindle cell type receiving postoperative adjuvant chemotherapy - Shohei Matsuo, MD; Emiko Tomita, MD; Kenjiro Fukuhara, MD, PhD; Akinori Akashi, MD, PhD; Yoshitane Tsukamoto, MD, PhD (Elsevier, 2019)
We experienced two cases of poorly differentiated synovial sarcoma (PDSS) arising from the chest wall. The first 42-year-old female patient was asymptomatic, but incidental chest roentgenogram showed a chest wall mass about 5-cm in maximal diameter with extrapleural sign. The chest wall mass was removed at other hospital. A tentative pathological diagnosis was mesothelioma with small cell features. After several courses of chemotherapy consisting of carboplatin and pemetrexed, the tumor recurred. On recurrence, the patient was referred to our hospital. Under the provisional diagnosis of recurrence of mesothelioma, a left extrapleural pneumonectomy (EPP) was performed. The tumor cells both in the surgical specimen of EPP and in previous surgical specimen at the first removal at other hospital consisted of small round cells. The differential diagnoses included Ewing sarcoma/primitive neuroectodermal tumor, PDSS (a small cell variant) and mesothelioma with small cell features. The immunohistochemical study showed no definite results. Further genetic testing showed the presence of SS18-SSX1, SS18-SSX2 and SS18 split signals and the absence of EWSR1-Fli1, EWSR1-ERG or EWSR1 split signals. The definite pathological diagnosis was PDSS, small cell variant. Additional chemotherapy, radiation therapy and molecular target therapy using pazopanib were done. However, the female patient died due to the disease progression 4 years after the first tumor removal. The other 44-year-old female patient is a recent case. Although she was asymptomatic, a rapidly growing mass (15 mm to 45 mm in maximal diameter within 3 months) arising from the right chest wall adjacent to the right apex of the lung was seen with extrapleural sign. Under the suspicious diagnosis of malignant neoplasm, tumor was removed without prior biopsy. The tumor cells showed herringbone-fibrosarcomatous features. Under the suspicious pathological diagnosis of PDSS, a high-grade spindle cell variant, genetic testing was performed. As the result, SS18-SSX1 fusion gene and positive SS18 split signals were identified. The pathological diagnosis was confirmed. The second patient has received 5 cycles of adjuvant anthracycline-ifosfamide chemotherapy. She is now alive without disease relapse. These two cases above are radiologically similar and both belong to the category of PDSS, although precise histopathological features are different. Considering the malignant potential of PDSS, close attention should be paid to the second patient. Keywords: Chest wall, Poorly differentiated synovial sarcoma, Sarcomatoid mesothelioma, Pazopanib